1997
DOI: 10.1200/jco.1997.15.7.2510
|View full text |Cite
|
Sign up to set email alerts
|

Dose-finding study and pharmacokinetics of epirubicin and paclitaxel over 3 hours: a regimen with high activity and low cardiotoxicity in advanced breast cancer.

Abstract: Our study demonstrates that (1) the MTD is epirubicin 90 mg/m2 and paclitaxel 200 mg/m2; (2) no clear relationship exists between pharmacokinetic data of paclitaxel and myelosuppression, while the increase in the dose of paclitaxel is associated with a reduction in epirubicinol plasma levels; and (3) the association is feasible, with low cardiotoxicity, and has a high activity in metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
3
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 19 publications
4
43
3
2
Order By: Relevance
“…Results from these studies, as well as an analysis on the cardiac safety of the ET combination, have been reported individually (Conte et al, 1997(Conte et al, , 2001aGennari et al, 1999;Baldini et al, 2002) and all the data have been prospectively collected at the Trial Office of Pisa Department of Medical Oncology (ET and gemcitabine plus epirubicin plus taxol (GET) trials) or at the Trial Centre of the National Cancer Research Institute of Genoa (Manta and MIG 6 trials).…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…Results from these studies, as well as an analysis on the cardiac safety of the ET combination, have been reported individually (Conte et al, 1997(Conte et al, , 2001aGennari et al, 1999;Baldini et al, 2002) and all the data have been prospectively collected at the Trial Office of Pisa Department of Medical Oncology (ET and gemcitabine plus epirubicin plus taxol (GET) trials) or at the Trial Centre of the National Cancer Research Institute of Genoa (Manta and MIG 6 trials).…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…However, despite the lack of statistical significance, probably due to the limited number of cardiac events registered, the trends, we observed, are different in the different subpopulations. While in anthracycline-naïve patients the cardiac risk is quite low whatever may be the randomisation arm, according to the published data on the safety of concomitant Epirubicin/Paclitaxel (Conte et al, 1997), in patients previously exposed to adjuvant Epirubicin and randomised to receive E þ P, the risk of cardiotoxicity gradually increases during chemotherapy, and from 20% after the fourth course, it rises steeply to 75% or more after the eighth course (cumulative dose 1080 mg m À2 in some patients). On the contrary, patients randomised to E-P showed a modest increase in cardiotoxicity during the four initial courses of high-dose Epirubicin (up to 21%), but the risk stabilizes, and no additional event was reported during, or after, four courses of high-dose Paclitaxel (250 mg m À2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, Paclitaxel seemed to be actively responsible for enhanced cardiotoxicity of the combination since it significantly modified the pharmacokinetics of Doxorubicin and its cardiotoxic metabolites (Gianni et al, 1995a, b;Gehl et al, 1996). At comparable dose levels, Epirubicin is significantly less cardiotoxic than Doxorubicin (Perez et al, 1991) and Paclitaxel seems to play a minor role on Epirubicin metabolism when the two drugs are used in combination (Conte et al, 1997, Danesi et al, 2002; this data could explain, in part, the more favourable cardiotoxic profile reported for the douplet Paclitaxel/Epirubicin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Anthracycline-and taxane-based chemotherapy regimens are active as front-or second-line treatment options in patients with MBC resulting in high response rates (Gianni et al, 1995;Ravdin et al, 1995;Conte et al, 1997;Mavroudis et al, 1999). For patients who have failed to respond or relapse early after the taxane/anthracycline regimens, the prognosis is poor since few drugs are still active in this setting (Porkka et al, 1994).…”
mentioning
confidence: 99%